Morphometric analysis of hard palate and its clinical importance - Subhash M Gujar; Sunil G Oza (Wolters Kluwer Medknow Publications, 2018)
Background & aim: The study of hard palate is important because of its role in speech articulation. The aim of the present study was to determine the palatine length, breadth and position of greater palatine foramen[GPF]. Material & Method : 50 dried, unsexed skulls from C U Shah Medical College, Surendranagar were studied. Palatine length, breadth & distance of Greater palatine foramen[GPF] to middle maxillary sutures[MMS] were measured with help of vernier caliper. Result : Mean palatine length and breadth were 47.10±3.34mm & 36.26+2.55mm respectively. The distance of GPF from MMS was 16.55 mm & 16.57 mm on right and left side respectively. The palatine index showed that 68% of the skulls had narrow [Leptostaphyline], 20% intermediate [Mesostaphyline] & 12 % wide [Brachystaphyline] palates. Conclusions: These observations would be helpful for anatomists, anthropologists and also to surgeons for various surgical procedures on hard and soft palates.